Psychometric properties of postnatal accumulated fatigue scale validity and reliability - Kirca, Ayca Solt; Gul, Derya Kanza; Sener, Nurdilan (Wiley, 2023)
Objective: Fatigue is a common adverse experience in postpartum women and can seriously affect maternal and infant health and quality of life. The aim of this study was to adapt the validity and reliability of the postnatal accumulated fatigue scale (PAFS) for postpartum mothers.Methods: The sample of the cross-sectional methodological study consisted of 140 postpartum mothers. Data were collected between July and December 2020. Tools used for data collection were the mother information form, Edinburgh postpartum depression scale, and the PAFS.Results: As a result of exploratory factor analysis, it was determined that PAFS consisted of 13 items, 6 items in the Physical Fatigue subdimension, 4 items in the Emotional subdimension, and 3 items in the Cognitive subdimension. The three-factor scale structure supported confirmatory factor analysis. On the total scale, Cronbach's a was found to be 0.91.Conclusions: Based on the study results, the Turkish language version of the PAFS is valid and reliable for postpartum mothers. This scale can be used safely by health professionals in postpartum units.
Keywords: fatigue; postnatal; postpartum period; reliability; validity; women